2018
DOI: 10.1002/acr.23270
|View full text |Cite
|
Sign up to set email alerts
|

Septic Arthritis in Emergency Departments in the US: A National Study of Health Care Utilization and Time Trends

Abstract: Comorbidities were associated with a higher risk of hospitalization after an ED visit for septic arthritis, but not higher ED charges. No time trends in ED visit incidence, ED charges, or hospitalization rate for septic arthritis from 2009-2012 were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In addition, OA consumes a substantial amount of healthcare resources and costs. Studies have demonstrated that OA was associated with higher risk of hospitalization and emergency department charges among those who present in the emergency room for other reasons [25,26]. The average direct cost of OA in Canada increased from $577 to $811 per patient/year between 2003-2010, primarily due to joint replacement surgery costs [27].…”
Section: Impact Of Osteoarthritismentioning
confidence: 99%
“…In addition, OA consumes a substantial amount of healthcare resources and costs. Studies have demonstrated that OA was associated with higher risk of hospitalization and emergency department charges among those who present in the emergency room for other reasons [25,26]. The average direct cost of OA in Canada increased from $577 to $811 per patient/year between 2003-2010, primarily due to joint replacement surgery costs [27].…”
Section: Impact Of Osteoarthritismentioning
confidence: 99%
“…In fact, it has been estimated that 30 percent of all patients surviving SA suffer from chronic joint damage eventually causing invalidity ( 14 , 15 ). The mortality of this disorder remains continuously high and research data defining the pathogenesis of SA are limited ( 11 , 16 18 ). In particular, the significance of pre-existing joint disorders for the onset and progression of SA remains obscure, despite epidemiological studies pointing toward autoimmune joint diseases as risk factors ( 13 , 16 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Septic arthritis is an orthopedic emergency requiring urgent joint washout and antibiotics. On average, admissions for septic arthritis typically last a week [6]. Given the time course of symptom resolution, negative cultures, no recent sexual history, and negative gonorrhea and chlamydia testing, gonococcal and non-gonococcal arthritis was less likely.…”
Section: Discussionmentioning
confidence: 99%